(3GdESJfUGQ aj CfSGH GdCfUGQs - (3YHO Gddg Hf CMeO Hf eMeO Hf bOGeI GdLeGYjdj GdebOSj Ke GdOeTbj GdMfHdj, ehab GdOjf GHf bOGeI , J (B620 (3gs
(3ChdgG (B:s
(3GdMeO ddg GdcQje GdhgGH (B, (3gPG cJGH PcQJ ajg CfSGH GdUMGHI ef GdCfUGQ hWQaG ef CNHGQge Ydi SHjd GdGNJUGQ s
(3BNQgG (B:s
(3JQLeI EeQCI YHO Gddg Hf QhGMg Hbhdg (B: (3abGdJ EeQGJg UOb Gddg hcPHJ Yjfi hcGfJ dGJMaX GdbQBf Je GdcJGH s
(3HgG fXGe GdJYbjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B30 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B459s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(485 (3b(B) s
Keywords: (3GdJGQjNs